PENGARUH GAYA MENGAJAR GURU DAN GAYA BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA: STUDI KASUS SMK NEGERI 1 KINALI - Anggelina, Putri Anggun; Darman, Regina Ade; Nurdin, Bernediv Nurdin (Information Technology Education Department, 2023)
This study is to determine the effect of teacher teaching style and student learning style on student learning outcomes in class XI TJKT in KK1 (Network Planning and Addressing) subject. This research was conducted at SMK N 1 Kinali. The sampling technique used was saturated sampling. This research is a type of quantitative research with data collection techniques through questionnaires, tests, and documentation. Based on the partial research results, the teacher's teaching style variable obtained a significant value of 0.773>0.05, which means H0 is accepted, and Ha is rejected. The student learning style variable obtained a significant value of 0.001<0.05 means H0 is rejected, and Ha is accepted. Furthermore, based on the results of simultaneous research, the value of FHitung>FTabel is 5.677>3.147 and a significance of 0.005<0.05, thus H0 is rejected, and Ha is accepted. As for the effect of learning outcomes after knowing the teacher's teaching style and student learning style, where the teacher can apply a teaching style that suits the student's learning style. So, the conclusion is that there is a significant influence between the teacher's teaching style and student learning style on the learning outcomes of XI TJKT class students in KK1 (Network Planning and Addressing) subject at SMK Negeri 1 Kinali.